х+у=12 х=12
8х+3у=0 3у=-8х у=-8х/3 минус 8х-числитель 3 знаменатель
12а- b=17 - b=17-12a b=12a-17 умножили на (-1)
7k-2p=14 -2p=14-7k -p=7(2-k)/2 умножаем на (-1) р=-7(2-k)/2
3x-5y= -15 3x=5y-15 x=5(y-3)/3 x=5/3 (y-3)
-4x+7y= -28 7y=-28+4x y=4(-8+x)/7 y=4/7(x-8)
12m+3n= -4 12m= -4 -3n m=-(4+3n)/12
-24a-6b=10 -24a=10+6b -a=2(5+3b)/24 a= -(5+3b)/12
2x+5y=17 2x=17-5y x=17-5y /2 17-5y делить на 2,чтоб понятнее было
5 m-10n=45 5(m-2n)=45 m-2n=9 m=9+2n cокращаем обе части на 5
х+у=12 х=12
8х+3у=0 3у=-8х у=-8х/3 минус 8х-числитель 3 знаменатель
12а- b=17 - b=17-12a b=12a-17 умножили на (-1)
7k-2p=14 -2p=14-7k -p=7(2-k)/2 умножаем на (-1) р=-7(2-k)/2
3x-5y= -15 3x=5y-15 x=5(y-3)/3 x=5/3 (y-3)
-4x+7y= -28 7y=-28+4x y=4(-8+x)/7 y=4/7(x-8)
12m+3n= -4 12m= -4 -3n m=-(4+3n)/12
-24a-6b=10 -24a=10+6b -a=2(5+3b)/24 a= -(5+3b)/12
2x+5y=17 2x=17-5y x=17-5y /2 17-5y делить на 2,чтоб понятнее было
5 m-10n=45 5(m-2n)=45 m-2n=9 m=9+2n cокращаем обе части на 5